ANALYSIS OF SEED HULL OF MEDICINAL PLANTS OF FAMILY FABACEAE - Mehra, Yashwant Kumar; De, Kantishree (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Cajanus cajan, Lens culinaris and Phaseolus vulgaris are plants belonging to family fabaceae. In this present study seed hull extract of all above three medicinal plants were screened for antifungal, phytochemical and antioxidant activity. Antifungal activity screened against Candida albicans and Candida krusei by well diffusion method. The minimum inhibitory concentration (MIC) value against Candida albicans is 18mm at the concentration of 0.40 mg/ml. All these plant extracts contain carbohydrates, proteins and alkaloids. Phaseolus vulgaris showed higher free radical scavenging activity in comparison to Cajanus cajan and Lens culinaris determined by DPPH. All above three plant hull extracts could be beneficial for health purposes as all of them contain viz. carbohydrates, proteins sterols, alkaloids and flavonoids, and antioxidants which have non-toxic and eco-friendly properties. Keywords: Antifungal bioassay, Antioxidant, Minimum inhibitory concentration (MIC), Lens culinaris, Phaseolus vulgaris